Pseudocyst presenting as pseudoachalasia - S., Nishanth; Jain, Sudhir Kumar; Singh, Chandra Bhushan (International Surgery Journal, 2019)
Achalasia cardia is a primary motility disorder of esophagus which is due to loss of ganglion cells in myentric plexus, etiology of which is unknown. The condition causes dysphagia due to failure of relaxation of lower esophageal sphincter. Pseudoachalasia is a similar disorder which occurs usually due to adenocarcinoma of the cardia and also due benign tumors at this level. We present a rare case of pseudocyst of pancreas extending into mediastinum which mimics as pseudoachalasia.